1994
DOI: 10.2172/10102203
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Fuel Component Contribution to Engine Emissions and Performance: Final Report

Abstract: This publication was reproduced from the best available camera-ready copy submitted by the subcontractor and received no editorial review at NREL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Fuel aromatic content has also been found to reduce each of the regulated emissions (Erwin et al, 1994;Schaberg et al, 1997;Cowley et al, 1993). In the case of PM, it has been shown that at low engine speeds and loads particulate PAH emissions can be accounted for by unburned fuel PAH, although at high speeds and loads, there is evidence of additional sources of PAH.…”
Section: Aromatic Contentmentioning
confidence: 99%
“…Fuel aromatic content has also been found to reduce each of the regulated emissions (Erwin et al, 1994;Schaberg et al, 1997;Cowley et al, 1993). In the case of PM, it has been shown that at low engine speeds and loads particulate PAH emissions can be accounted for by unburned fuel PAH, although at high speeds and loads, there is evidence of additional sources of PAH.…”
Section: Aromatic Contentmentioning
confidence: 99%